Data Warehouse Perusahaan Bidang Geomatika dan Manajemen Informasi - Hapsari, Ambar Tri (Jurnal Informatika Universitas Pamulang, 2021)
PT. Duta Astakona Girinda is a company in the field of geomatics and spatial information management. This company was founded in early 1987 to provide consulting services for spatial information management applications, hardware, software, implementation and communication. As the experience of PT. Duta Astakona Girinda as an information and communication technology management application consulting service provider, continues to innovate. Providing services such as mapping planning, thematic maps of various needs, cartography, digitizing services, scanning, plotting. This company also provides GIS market application development services, GIS and MIS integration. Other services include conducting training, seminars and creating a spatial database. The company needs a warehouse information system to make it easier for warehouse administrators to manage incoming and outgoing goods at PT Duta Astakona Girinda. The role of this Information System is also inseparable from the users of equipment that are able to overcome the inability of human labor. The desktop application created here is internal in nature, which can only be accessed by employees.